Robust optima and tolerance ranges of biological indicators: a new method to identify sentinels of global warming. Issue 1 (7th December 2013) - Cristóbal, Elena; Ayuso, Sergio Velasco; Justel, Ana; Toro, Manuel
Abstract: This study aims to introduce the robust optimum (RO) method as an alternative to the classical weighted averaging (WA) method for estimating the ecological optimum as well as the optimum and tolerance ranges of a taxon with respect to an environmental variable in limnological studies. The RO method is based on robust location and scale estimates rather than on the mean and the standard deviation used by the WA method. The results of our study support the well‐known fact that the presence of outliers and the asymmetry of the distribution of the environmental variable might cause a significant effect on the WA‐calculated ecological optimum as well as on tolerance ranges. We compared both methods through the identification of potential biological indicators of global warming. Biological data included several benthic, oligostenotherm macroinvertebrate families inhabiting the Júcar River Basin (JRB, eastern Spain). The results of this comparison suggest that the RO method is more appropriate for estimating the distribution of taxa and, consequently, that it provides more realistic information for identifying potential sentinels of global warming in running aquatic systems. Currently, the identification of such sentinels is a goal for several environmental protection laws, such as the European Union Water Framework Directive.